Do nurses and doctors feel that nurse prescribing has achieved its goals? A review of the literature. - Leonard, Amy (2009)
Do nurses and doctors feel that nurse prescribing has achieved its goals? A review of the literature. Background: In the UK, the number of nurses able to prescribe medicines has advanced rapidly in line with Government policy. Whilst a number of studies have been conducted on nurse prescribing, review and synthesis of the findings from doctor and nurse perspectives had not been undertaken. Aim: To critically appraise published studies to identify key findings about the impact and effectiveness of nurse prescribing; using the perceptions of nurses and doctors. Methods: A review of the literature on nurse prescribing (after 2000) in the UK was undertaken using electronic databases and specified search terms. Results: 8 publications were included in this review. Four general themes emerged from the literature: Patient centred care, Nursing workforce, General benefits to nurse prescribing and prescribing difficulties. Nurses and doctors were generally positive about nurse prescribing, which shows that it is meeting the aims of nurse prescribing: saving the patient time, increasing role satisfaction for nurses, and reducing doctor’s workloads. However some barriers to nurse prescribing were acknowledged, these centred on the restrictions of the Nurse Prescribers Formulary, increased workload for nurses and concerns about the adequacy of nurses pharmacological knowledge. Conclusions: This review shows that nurse prescribing has generally been evaluated positively; however there are under-researched issues such as research regarding the most recent nurse prescribing from the whole BNF. Relevance to clinical practice: This literature review focuses on a clinical issue central to current and future nursing roles.